Overview of Microorganisms Causing Urinary T ract Infections at Cut Meutia General Hospital, North Aceh, Indonesia - Santoso, Hidayat; Ali, Zulfikar (Sriwijaya Journal of Internal Medicine, 2023)
Introduction: Urinary tract infection (UTI) is a general term that refers to the presence of microorganisms in the urine. Bacteria and fungi are the causative agents of urinary tract infections, which can be found in the urine of someone who is indicated to be suffering from a urinary tract infection. This study aimed to provide an overvie w of microorganisms that cause urinary tract infections in Cut Meutia General Hospital, North Aceh, Indonesia. Methods: This study is a descriptive observati onal study. A total of 100 research subjects participated in this study. Data analysis on the distribution of microorganisms that cause UTIs was carried out in a univariate. Results: The majority of microorganisms that cause urinary tract infections are Escherichia coli. In addition, other microorganisms as the cause of urinary tract infections are Klebsiella pneumoniae, Acinetobacter baumannii, Proteus mirabilis, Klebsiella oxytoca, and Pseudomonas aeruginosa. Conclusion: Escherichia coli is the most common microorganism that causes urinary tract infections at Cut Meutia General Hospital, North Aceh, Indonesia.